Data behind Figures in "Peroxy acetyl nitrate (PAN) measurements at northern midlatitude mountain sites in April: a constraint on continental source–receptor relationships" - Fiore, Arlene M.; Fischer, Emily V.; Milly, George P.; Pandey Deolal, Shubha; Wild, Oliver; Jaffe, Dan; Staehelin, Johannes; Clifton, Olivia E.; Bergmann, Dan; Collins, William; Dentener, Frank; Doherty, Ruth M.; et al. (Colorado State University. Libraries, 2018)
Abundance-based model evaluations with observations provide critical tests for the simulated mean state in models of intercontinental pollution transport, and under certain conditions may also offer constraints on model responses to emission changes. We compile multiyear measurements of peroxy acetyl nitrate (PAN) available from five mountaintop sites and apply them in a proof-of-concept approach that exploits an ensemble of global chemical transport models (HTAP1) to identify an observational "emergent constraint". In April, when the signal from anthropogenic emissions on PAN is strongest, simulated PAN at northern midlatitude mountaintops correlates strongly with PAN source–receptor relationships (the response to 20 % reductions in precursor emissions within northern midlatitude continents; hereafter, SRRs). This finding implies that PAN measurements can provide constraints on PAN SRRs by limiting the SRR range to that spanned by the subset of models simulating PAN within the observed range. In some cases, regional anthropogenic volatile organic compound (AVOC) emissions, tracers of transport from different source regions, and SRRs for ozone also correlate with PAN SRRs. Given the large observed interannual variability in the limited available datasets, establishing strong constraints will require matching meteorology in the models to the PAN measurements. Application of this evaluation approach to the chemistry– climate models used to project changes in atmospheric composition will require routine, long-term mountaintop PAN measurements to discern both the climatological SRR signal and its interannual variability.
This archive contains data used for figures in "Peroxy acetyl nitrate (PAN) measurements at northern midlatitude mountain sites in April: a constraint on continental source–receptor relationships." Included are data from model simulations of the year 2001, and observations spanning the years 1995-2010. Data is primarily in text file format aside from a collection of gridded modeled data in netCDF format. Full contents are described in README file.
Department of Atmospheric Science
Keywords: PAN; Peroxy acetyl nitrate; atmospheric chemistry; emergent constraint; intercontinental transport; air pollution; hemispheric transport; ozone